2006
DOI: 10.1002/ana.20757
|View full text |Cite
|
Sign up to set email alerts
|

UCHL‐1 is not a Parkinson's disease susceptibility gene

Abstract: Based on the current evidence, the UCHL-1 gene does not exhibit a protective effect in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 26 publications
0
70
1
1
Order By: Relevance
“…Subsequent studies failed to replicate the ILE93-MET variant in familial and sporadic forms of Parkinson disease and identified only one other common UCHL1 variant, a serine to tyrosine (SER18TYR) polymorphism (20,21). Although a protective effect for the UCHL1 SER18TYR variant against Parkinson disease was initially suggested, several subsequent association studies yielded conflicting results (22)(23)(24). In the family presented here, neither the patients homozygous for the UCHL1 GLU7ALA variant nor their heterozygous parents or siblings exhibited Parkinsonian features on neurological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies failed to replicate the ILE93-MET variant in familial and sporadic forms of Parkinson disease and identified only one other common UCHL1 variant, a serine to tyrosine (SER18TYR) polymorphism (20,21). Although a protective effect for the UCHL1 SER18TYR variant against Parkinson disease was initially suggested, several subsequent association studies yielded conflicting results (22)(23)(24). In the family presented here, neither the patients homozygous for the UCHL1 GLU7ALA variant nor their heterozygous parents or siblings exhibited Parkinsonian features on neurological examination.…”
Section: Discussionmentioning
confidence: 99%
“…UCH-L1 has also been identified as a component of several inclusion bodies characteristic of neurodegenerative diseases including Lewy bodies (14). A polymorphism in the UCH-L1 gene, resulting in an S18Y substitution at the amino acid residue level, has been reported to be associated with decreased risk of PD in certain populations but not in other populations (15,16). We have also reported that UCH-L1 I93M and carbonyl-modified UCH-L1, which is associated with sporadic PD (17), display shared aberrant properties (13), suggesting that carbonyl-modified UCH-L1 constitutes one of the causes of sporadic PD.…”
mentioning
confidence: 99%
“…Maraganore et al [8] found an inverse association between the UCH-L1 S18Y variant and PD in a sample of combined Asian and white participants. Two years later, Healy et al [10] conducted a meta-analyses of 9 case-control studies in white individuals and did not find a protective effect of the UCH-L1 gene in PD. A recent meta-analysis performed by Ragland et al [9] showed a statistically significant association between the S18Y variant and reduced risk of PD in Asian populations in a recessive model (YY vs. SY + SS, p = 0.0006).…”
Section: Discussionmentioning
confidence: 99%
“…The Ser 18 Tyr (S18Y; C54A) polymorphism in exon 3 has also been reported as a potential candidate [7], but its association with PD remains controversial. Some studies found a protective effect of the S18Y polymorphism on PD [8,9], whereas other studies detected no association between S18Y and PD [10]. Recently, Miyake et al [11] performed studies in a Japanese population and revealed that the UCH-L1 S18Y variant is a risk factor for sporadic PD.…”
Section: Introductionmentioning
confidence: 99%